Pengembangan Bahan Ajar Ipa Berbasis Interactive Learning Untuk Meningkatkan Kemampuan Mahasiswa PGSD FIP UNM - muslimin muslimin; Muhammad Amran (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to develop and implement and examine the extent of science learning materials based on interactive learning to improve the ability of students of PGSD FIP UNM. The subjects of this study were PGSD students who programed a basic concept course for Science 1 academic year 2019/2020. This research follows the stages of developing the ADDIE model which consists of five stages namely Analyze, Design, Development, Implementation, and Evaluation. The results of the study indicate that the development of interactive learning-based teaching materials to improve the ability of PGSD FIP UNM students is in the very good category and the level of effectiveness of the use of teaching materials is very good based on the response of lecturers and students.